Essays on non-financial information disclosure, performance, and strategy - Pizarro Veloso, Gabriela Beatriz (2023)
This thesis consists of three chapters on sustainability reporting better known as Non-Financial Information (NFI) Disclosure, focusing on the role of imitation as a driver of environmental, social, and governance (ESG) practices, firms’ mandatory disclosures of NFI, and firms’ optimal distinctiveness in ESG practices. The first chapter responds to the call in the strategy literature for more research on convergence in sustainability practices and the role that individual firms play in this process by determining which peer characteristics are more influential when firms decide which peers to imitate. In addition to examining industry determinants, this study investigates the country-level factors that may impact a firm's tendency to mimic influential peers' ESG disclosure scores. I theorised that firms are inclined to mimic influential peers within their industry regarding ESG disclosure, especially in uncertain environments. Using a global sample of 9,202 firms over a period of nine years, I find support for the hypotheses. The results demonstrate that firms imitate their peers with superior information or influence when uncertainties about the outcome of a decision are present such as the disclosure of ESG practices in developing regions and when mandatory regulations are present. These results underscore the need for institutional theory to consider the institutional context when investigating the determinants of ESG disclosure. Chapter 2 examines the effects of mandatory NFI disclosure on firm value. In 2018, Directive 2014/95/EU was introduced in the European Union (EU) and European Economic Area (EEA) countries, requiring large corporations to disclose non-financial information (NFI) related to environmental, social, and governance (ESG) practices. This study employs a fuzzy regression discontinuity design (RDD) to examine the market value implications of ESG disclosure in response to this regulatory change, using the adoption of Directive 2014/95/EU as a quasi-natural shock. The empirical analysis reveals a positive relationship between mandated ESG disclosure and firm valuation for entities complying with the directive. Furthermore, it can be observed that this effect is more pronounced for firms subject to increased public scrutiny. These findings emphasize the potential benefits of increasing transparency regarding corporate ESG practices and highlight the moderating role of stakeholder pressure in shaping the relationship between mandatory ESG disclosure and financial performance. The last chapter investigates the impact of distinctiveness in ESG material information on firm value and explores how other sources of legitimacy can influence this relationship. Using ESG materiality scores from the Bloomberg database and listed EU firms’ data from 2016 to 2020, the findings suggest that as ESG disclosure becomes an institutionalised practice among European firms due to Directive 2014/95/EU, a positive relationship between the extent of material ESG disclosure and firm value occurs, with the highest and lowest levels of distinctiveness yielding the most pronounced effects. Furthermore, the findings indicate that analyst earnings forecasts play a crucial role in granting an additional source of legitimacy for firms, providing a buffer-effect that allows them to exhibit a certain degree of nonconformity without compromising their overall legitimacy.